Confidence in treatment is contributing to quality of life in autoimmune liver diseases. The results of ERN RARE‐LIVER online survey. (3rd October 2022) - Wunsch, Ewa; Krause, Linda; Gevers, Tom JG; Schramm, Christoph; Janik, Maciej K.; Krawczyk, Marcin; Willemse, José; Uhlenbusch, Natalie; Löwe, Bernd; Lohse, Ansgar Wilhelm; Milkiewicz, Piotr
Abstract: Background and Aims: Autoimmune liver diseases (AILDs) are associated with impaired health‐related quality of life (HrQoL). The aim of this project was to identify potentially modifiable factors related to HrQoL in a large transnational cohort of patients with AILDs. Methods: A cross‐sectional online survey was conducted on patients with autoimmune hepatitis (AIH), primary biliary cholangitis (PBC) or primary sclerosing cholangitis from 15 European countries. HrQoL was measured with EQ‐5D‐5L and EQ visual analogue scale (EQ‐VAS) and analysed in relation to demographic, psychosocial, disease‐ and treatment‐related factors. A Patient Health Questionnaire‐2 score >3 indicated relevant depression. Multivariable linear regression analyses were used to identify potentially modifiable factors associated with HrQoL and confidence in treatment whilst adjusting for known confounders. Results: A group of 1178 European patients (79% female, mean age 48 ± 14 years) participated in the study. HrQoL was impaired in all three diseases (mean EQ‐5D‐5L = 0.75, mean EQ VAS = 68.9), most markedly in PBC (mean EQ‐5D‐5L = 0.73, mean EQ‐VAS = 66.2). Relevant depression, which was detected in 17% of patients, was prominently associated with impaired HrQoL. In the regression analysis, treatment confidence was identified as an important modifiable factor positively contributing to HrQoL. This influence was observable even after adjusting for other covariates including depression. Management in a transplant centre, treatment with azathioprine in AIH, and with ursodeoxycholic acid in PBC, was associated with increased treatment confidence. Finally, improved patient‐physician relationships contributed to treatment confidence. Conclusion: Treatment confidence is a relevant modifiable determinant of HrQoL and should be further investigated to improve the standards of care for patients with AILDs.